Effect of Die Angle on Stress Distribution in Extrusion Process of Aluminum Rod - Mohammed, Rafid Jabbar (Basrah Journal for Engineering Sciences, 2014)
Type of metal flow and stress distribution in metal extrusion process is a highly complex for the complicated die design. In this work a finite element simulation of Al-1100 rod extrusion was successfully achieved using the commercial finite element code Deform-3D.The results show that the finite element model was successfully simulate the stress distribution in the direct rod extrusion of Al-1100.Besides that the optimum die angle reduces the magnitude of normal, shear, and effective stresses. We can conclude from this studythat maximum stresses occour when the rod is with contact with the die at exit stage.